Engagement in a Science Museum – The Role of Social Interactions. Issue 1 (2nd January 2019) - Shaby, Neta; Ben-Zvi Assaraf, Orit; Tal, Tali
Abstract: This qualitative research explores the interactions of elementary school students during free-choice activity with science museum exhibits. The study participants were 39 students, who visited a science museum on six occasions during a three-year-period (from 4 th to 6 th grades). Our study showed that most interactions around exhibits are social in nature. Within these social interactions, students mainly discuss the technicalities of operating the exhibits and rarely engage with their scientific content. On occasion, exhibits are no more than settings for social interactions that could equally occur, for example, in the schoolyard. The main implications of this study concern exhibit design and pedagogy. Because students find ways to create their own social interactions in museum settings, museum pedagogy should leverage this social interaction into cognitive engagement with the scientific content of exhibits.